2022
DOI: 10.1111/bcp.15279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pharmacist interventions on cardiovascular risk factors and outcomes: An umbrella review of meta‐analysis of randomized controlled trials

Abstract: Aims To grade the evidence from published meta‐analyses of randomized controlled trials (RCTs) that assessed effects of pharmacist intervention on cardiovascular risk factors and cardiovascular outcomes. Methods MEDLINE, Embase, and the Cochrane Library were searched from database inception to July 2021. Meta‐analyses of RCTs were eligible. Quality of evidence were assessed by GRADE approach. Results From 9308 publications, 149 full‐text articles were evaluated for eligibility, and 24 studies with 85 unique me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The results of our study showed that the pharmacy services group had a significantly higher rate of treatment improvement and efficiency than the group without pharmacist participation ( p < 0.05). A meta-analysis on cardiovascular disease showed a similar finding: pharmacist services provides a wide range of benefits in cardiovascular disease management, from controlling risk factors to improving medication adherence and, in some settings, reducing morbidity and mortality ( Rattanavipanon et al, 2022 ). No significant effect of the pharmacist services on the cure rate was observed in this study, partly because CNSI have a long course of treatment, making it difficult to achieve the desired treatment outcome during hospitalization, and partly because of our strict cure criteria.…”
Section: Discussionmentioning
confidence: 87%
“…The results of our study showed that the pharmacy services group had a significantly higher rate of treatment improvement and efficiency than the group without pharmacist participation ( p < 0.05). A meta-analysis on cardiovascular disease showed a similar finding: pharmacist services provides a wide range of benefits in cardiovascular disease management, from controlling risk factors to improving medication adherence and, in some settings, reducing morbidity and mortality ( Rattanavipanon et al, 2022 ). No significant effect of the pharmacist services on the cure rate was observed in this study, partly because CNSI have a long course of treatment, making it difficult to achieve the desired treatment outcome during hospitalization, and partly because of our strict cure criteria.…”
Section: Discussionmentioning
confidence: 87%
“…In a systematic review conducted by Chiazor, Evans [13], community pharmacist's interventions on diabetes and hypertension revealed favourable clinical outcomes [13]. Similar findings reported substantial improvement on hypertension, diabetes, hyperlipidaemias, obesity, and smoking cessation following community pharmacists' interventions [10][11][12]14,15]. The identified roles of community pharmacist suggest that they can provide expanded services and stand an opportunity to improve CVD burden in Lesotho.…”
Section: Plos Onementioning
confidence: 83%
“…Community pharmacists can provide both effective population-based and individualized primary healthcare services. The effectiveness of community pharmacist' roles in primary healthcare interventions is demonstrated in smoking cessation programs, health promotion, and medication therapy management and adherence services [10][11][12][13][14][15]. Thus, community pharmacy presents an opportunity in primary healthcare setting for effective prevention and control of CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses provide strong evidence for the positive impact of pharmacist interventions on cardiovascular risk factors and outcomes [ 80 ]. The evidence for secondary prevention of stroke from this systematic review is weaker due to the heterogeneity of the studies.…”
Section: Discussionmentioning
confidence: 99%